(untitled) (London Journal of Medical and Health Research, 2026)
Diabetic foot is a major chronic complication of diabetes mellitus and represents a leading cause of hospitalisation, infection and non- traumatic lower limb amputation worldwide. The pathogenesis is multifactorial primarily involving peripheral neuropathy, peripheral arterial disease, impaired immunity and poor glycemic control which together predispose patients to ulceration and delayed wound healing. This review of literature aims to summarise current evidence regarding epidemiology, risk factors clinical evaluation and treatment strategies for diabetic foot disease. The literature consistently demonstrates that early identification of at-risk patients through routine screening and structured risk stratification significantly reduces ulcer occurrence. Management of established diabetic foot ulcers requires a multi-disciplinary approach combining glycemic control, infection management using culture guided antimicrobial therapy, regular wound debridement, appropriate wound dressings and appropriate offloading techniques.In patients with associated ischaemia, timely vascular assessment followed by endovascular or surgical revascularisation is critical for limb salvage. Advanced adjunctive therapies including negative pressure wound therapy, bioengineered skin substitutes and growth factor- based treatments have shown beneficial outcomes in selected cases. Overall, comprehensive preventive programs and standardised multidisciplinary treatment protocols remain essential for reducing amputation rates and improving functional outcomes in patients with diabetic foot disease.